Wheelchair prototype controlled by position, speed and orientation using head movement. (April 2022) - González-Cely, Aura Ximena; Callejas-Cuervo, Mauro; Bastos-Filho, Teodiano
Graphical abstract: Abstract: A prototype that simulates a wheelchair was built using electronic commercial devices and software implementation with the aim to operate the prototype using head movement and analyzing the system response. The controllers were simulated using MATLAB® toolbox and Python™ libraries. The mean time response of the system with manual control was 37, 8 s. The mean orientation control response with constant speed was 36, 5 s and the mean orientation control response with variable speed was 44, 2 s in a specific route. The variable speed response is slower than constant speed due to head motion error. The system was rated such as" very good" by 10 participants using a System Usability Scale (SUS).